High levels of vascular endothelial growth factor (VEGF) and its receptors (VEGFR-1, VEGFR-2, neuropilin-1) are associated with worse outcome in breast cancer - Ghosh, S (2008)
Vascular endothelial growth factor has been shown to be upregulated in breast cancers. VEGFR-1 and VEGFR-2 are the principal mediators of its effects. Together with VEGFR-1 and VEGFR-2, neuropilin-1 may act as a co-receptor for VEGF. Although VEGF exerts important effects on endothelial cells, VEGFRs are likely present on tumor cells as well. We used AQUA to analyze tumor-specific expression of VEGF, VEGFR-1, VEGFR-2, and neuropilin-1 on a large cohort breast cancer tissue microarray. Two-fold redundant arrays were constructed from 642 cases of primary breast adenocarcinomas. Automated image analysis with AQUA was then performed to determine a quantitative expression score. Scores from redundant arrays were normalized and averaged. Kaplan-Meier survival analysis showed that high levels of VEGF, VEGFR-1, VEGFR-2, and neuropilin-1 were all significantly associated with survival (Miller Siegmeund corrected P value 0.0020, 0.0160, and 0.0320 respectively). In addition, VEGF and neuropilin-1 retained a significant association with survival independent of other standard prognostic factors. VEGF, VEGFR-1 and 2, and neuropilin-1 are expressed to varying degrees in primary breast cancers and have prognostic significance. Further study of the functional significance of this finding is warranted as well as the prognostic value of these biomarkers in other tumor microenvironment-specific compartments (e.g. vessels).